Sexual attitudes, sexual behaviors, and use of HIV prevention services among male undergraduate students in Hunan, China: a cross-sectional survey - Hehua Xu; Jiaying Xie; Zhizi Xiao; Hong Xiao; Xianhong Li; Lloyd Goldsamt; Ann Bartley Williams; Honghong Wang (BMC, 2019)
Abstract Background The dramatic increase in human immunodeficiency virus (HIV) infection among undergraduate students in China, especially among the male students, is alarming. This study aimed to describe sexual attitudes and behaviours and to examine the use of HIV prevention services and related factors among male undergraduate students in Hunan, China. Methods A cross-sectional survey was conducted from November 2017 to January 2018 among male students from three universities in Hunan, China. Self-administered questionnaires were uploaded online to collect data anonymously. HIV-related knowledge and sexual attitudes were assessed with the unified National AIDS Sentinel Surveillance Questionnaire and Sexual Attitude Scale, whereas sexual behaviours and use of HIV prevention services were examined with researcher-created questionnaires. HIV-related knowledge, sexual attitudes and behaviours, and use of HIV prevention services were described. Chi-square test and logistic regression were used to analyse the factors associated with the use of HIV prevention education services. P values ≤0.05 were considered significant. Results Of the 1431 respondents, 1068 (74.6%; 95% CI: 72.4-76.0%) used HIV prevention education services and 105 (7.3%) took HIV testing. The openness of sexual attitudes was moderate overall. About 299 (20.9%) of this sample had active sex partners, and 49 (16.4%) of them had sex with males. The consistent use of condoms was unsatisfactory among the sexually active students, especially among those with homosexual behaviours. Participants who were older in age (OR: 0.77, 95% CI: 0.70-0.86), who were university seniors (OR: 0.80, 95% CI: 0.70-0.91), who drank alcohol (OR: 0.71, 95% CI: 0.55-0.93), and who had open attitude towards paid sex (OR: 0.72, 95% CI: 0.54-0.95), were less likely to use HIV prevention education services. Conclusions Although male undergraduate students show open attitude to premarital sex and engage in risky sexual behaviours, their use of HIV prevention education services is unsatisfactory, particularly in terms of HIV testing. More comprehensive and specific education on HIV prevention and testing services should be designed and offered on campus.